The development of cloud modelling and motion analysis for virtual environment - Sunar, Mohd. Shahrizal; Daman, Daut; Kari, Sarudin; Mohd. Suaib, Norhaida; Bade, Abdullah (Universiti Teknologi Malaysia, 2005)
Modelling the natural phenomena such as clouds is one of the most challenging problems in computer graphics. The complexity of cloud formation, dynamics and light interaction makes real time cloud modelling a difficult task. The visual portrayal of the sky and cloud is a common requirement when rendering the outdoor scenes in computer graphics. The traditional way to create the sense of cloudy is by using the captured sky images as background. This main output of this project is a cloud modelling editor for designing cloud shapes namely RekAwan. The editor provides integrated environment for modelling volumetric clouds with particle system and surfaced based cloud using texture. This invention uses the newly developed randomized algorithm to fill the cloud volume with particle systems. Randomized method provides an efficient mean in modelling cloud particles data very quickly and filling the cloud volume space with particles randomly. The invention gives on-the-fly control over size of particles and number of particles and radius of particles in the system. This shows its suitability for real time virtual reality applications such as flight simulator and 3D games. The user can pass through the cloud with realistic visual effect. The completed 3D cloud model output from RekAwan can be easily imported into any OpenGL based virtual environment such as simulator, animation and games. RekAwan can also become plug-ins to current commercial 3D modeller software such as AutoCAD, 3D Studio Max, Maya and Rhino3D. The potential industries that highly use RekAwan are weather visualization, film, advertisement, games and flight simulator. This invention will cut the development cost of the industry such as simulator and entertainment. This product can be used effectively by 3D artists, designers and game developer to model cloud shapes easily through interactive user interface. It is simple to use, efficient and gives extensive control over the cloud shapes. RekAwan can also be used to model any other gaseous object such as smoke, haze and fog.